FRI0380 IL-6 Receptor Polymorphism in Polymyalgia Rheumatica; Relationship between ASP358ALA (T/G) Polymorphism of The Interleukin 6 Receptor (IL6R) Gene and Susceptibility and Severity of The Disease. (15th July 2016) - Boiardi, L.; Macchioni, P.; Farnetti, E.; Restuccia, G.; Pulsatelli, L.; Meliconi, R.; Salvarani, C.
Abstract : Background: In previous study, we found in Polymyalgia rheumatica (PMR) patients a significant correlation between the number of relapses and serum soluble interleukin-6 receptors (sIL-6R) concentrations at baseline and after 1, 3, and 12 months of therapy (1). The Asp358Ala (T/G) polymorphism of the interleukin 6 receptor (IL6R) was related with high levels of ser1um sIL-6R. Objectives: The Aim of our study was to evaluate the relationship between Asp358Ala (T/G) polymorphism of IL6R gene and susceptibility and severity of the PMR Methods: We studied 104 patients with pure PMR and 94 healthy controls. Serum levels of s-IL6R were evaluated using highly sensitive, commercial sandwich enzyme-linked immunosorbent assay kits (R&D Systems, Minneapolis, MN) according to the manufacturer's instructions. The IL6R Asp358Ala polymorphism (rs8192284) were molecularly genotyped Results: The distribution of allele and genotype frequencies did not differ significantly between PMR patients and healthy controls. Carriers of the Asp358Ala T allele (TT+GT) in PMR patients was 58.7% and in Healthy controls was 60.6% (p=0.78). Homozygosity for the T allele in PMR patients was 16.3% and in healthy control was 12.8% (p=0.48). However the patients and controls with this polymorphism presented higher level of serum s-IL6R. Finally, PMR patients with relapses/recurrences showed more frequently homozygosity for the T allele, but the difference with patients without relapses/recurrences was not statistically significant (p=0.07). Conclusions: Asp358Ala (T/G) polymorphism of the IL6R was related with high serum levels of s-IL6R; however, no correlation existed between this polymorphism and PMR susceptibily. Moreover, a bordeline correlation existed between TT homozygosity and relapses/recurrences in these patients. References: Pulsatelli L, Boiardi L, Pignotti E et al. Serum interleukin-6 receptor in polymyalgia rheumatica: a potential marker of relapse/recurrence risk. Arthritis Rheum. 2008;59:1147–54. Disclosure of Interest: None declared